Aplikasi Pupuk Organik Cair (POC) Urin Sapi Terhadap Pertumbuhan Semai Jelutung Rawa (Dyera lowii Hook. F) Pada Medium Gambut - Dwi Basliana Okta; M. Mardhiansyah; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Dyera lowii Hook.f is one of the forestry plants that can grow on peatlands. Dyera lowii plants are able to restore damaged peatlands such as forest fires. Cow urine contains growth aphrodisiacs that can be used as growth regulators including (IAA). Cow urine also has a positive influence on vegetative growth in plants. The purpose of this research is to determine effect and the best concentration of liquid organic fertilizer (LOF) of cow urine on the growth of Dyera lowii on peat media. The study used a Completely Randomized Design (CRD) method consisting of 4 treatments and 4 replications so that 16 units of the experiment would be obtained. The treatments are: K0 (without application of cow urine / control) K1 (application of cow urine concentration 20%) K2 (application of cow urine concentration 50%) K3 (application of cow urine concentration 80%). Data were further analyzed using variance, with SPSS software version 20.0. This test is carried out to find out if there is, at least one treatment that significantly affects the research. If there is, it must be continued with a test (DMNRT) with a level of 5%. Application of liquid organic fertilizer (LOF) of cow urine influences the growth of swamp Dyera lowii and the best concentration of  liquid organic fertilizer of cow urine to stimulate the growth of swamp Dyera lowii on peat media is a concentration of 20% (K1 treatment) increase in seedling height of 0.89 cm, dry weight of plants 0.74 gr and top root ratio 2.21. Keywords: Liquid organic fertilizer, cow urine, Dyera lowii Hook.f, peat media